TRANSFORMFORMASI DIGITAL DALAM PENDIDIKAN TINGGI: PENGARUH PENGGUNAAN AI, SELF-EFFICACY, DAN BUDAYA ORGANISASI TERHADAP KINERJA DOSEN - Kharisma, Fresha Kharisma; Irwan Adimas Ganda Saputra; Muhammad Fajar Wahyudi Rahman; Wenny Restikasari; Rasyidi Faiz Akbar; Mentari Septynaputri Widodo; Nurwinsyah Rohmaningtyas (Jurnal Bisnis Terapan, 2026)
Digital transformation in higher education is growing rapidly with the increasing use of Artificial Intelligence (AI) for learning and research activities. However, the success of AI implementation is greatly influenced by individual and organizational factors, including lecturer self-efficacy and organizational culture. This study aims to analyze the influence of AI use, self-efficacy, and organizational culture on lecturer performance in supporting Sustainable Development Goals (SDG) 4 on quality education. The research method uses a quantitative approach with a survey of 200 lecturers from various universities in Indonesia. Data were analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The results showed that AI (β = 0.342; p < 0.001), organizational culture (β = 0.248; p < 0.001), and self-efficacy (β = 0.354; p < 0.001) have a positive and significant effect on lecturer performance. However, the moderating effect of organizational culture on the relationship between AI and lecturer performance was not significant. This research emphasizes the importance of individual preparedness and organizational support in improving lecturer performance through the use of digital technology. These findings provide theoretical and practical contributions to the development of digital transformation policies in higher education.